26 Ghz Open Ended Air Gap Cavity Rlsa Antenna For Next Generation Broadband Wireless Access - Mohd Ibrahim, Imran; Abd Rahman, Tharek; Zakaria, Zahriladha (Universiti Teknikal Malaysia Melaka, 2016)
-